Epidemiological Studies of Microvascular and Macrovasacular Complications in Diabetes Mellitus Type - Shwetha, T.; Sri vidya, B.; Deekshitha, B.; Srihari, T.; Sameera, Amatul Ali; Amrohi, Nazia Lateef (Journal of Neonatal Surgery, 2025)
Aim: To perform an observational study on epidemiology of micro and macrovascular complications in diabetes mellitus type II. Objectives: To assess the occurrence and prevalence of micro and macrovascular complications in type 2 diabetes mellitus. Methodology: The study's methodology will be carried out in the internal medicine department of Gleneagles Aware Hospital in Bairamalguda, Saroornagar, Hyderabad, Telangana state. Over 6 month period with 100 patients individuals with microvascular problems. Patients aged 20 to 80 years, included with comorbid conditions in both genders. Patient demographics, medication records, laboratory tests, medical histories, and other relevant data were gathered using a well-designed data-collecting form for any in patients with diabetes mellitus who were experiencing problems. Results: The study findings revealed that most of the complications that occur in diabetic mellitus are macrovascular complications. Out of 100 subjects, 65 were males and 35 were female, 70 had macrovascular complications. In 70, (2) peripheral artery disease, (29) coronary artery disease, (39) ischemic stroke. And 30 are microvascular complications, (1) diabetic retinopathy, (4) diabetic neuropathy, (25) diabetic nephropathy. The age group between 61-70 (36) was found to have the most macrovascular and microvascular complications. Conclusion: The study concluded among 100 patients, who are affected by micro vascular and macrovascular complications in type 2 diabetes mellitus, are studied during the study period